A functional haplotype variant in the TBX22 promoter is associated with cleft palate and ankyloglossia. Issue 8 (31st July 2009) - Pauws, E; Moore, G E; Stanier, P
Abstract : Background: Mutations in the T-box transcription factor gene TBX22 are found in patients with X-linked cleft palate and ankyloglossia (CPX), and are reported in approximately 5% of all non-syndromic cleft palate patients. Clinical variability in CPX ranges from a mild or occult submucous cleft palate to a severe, complete cleft of the secondary palate. Aims: To explore the possibility that mutations lying outside of the TBX22 coding region might contribute to the phenotype, a non-coding upstream exon and its upstream regulatory region were investigated. Methods and results: We sequenced 137 patients with cleft palate without coding region mutations and 295 controls. While no unique mutations were identified, seven single nucleotide polymorphisms (SNPs) were noted. These variants segregate into four distinct haplotypes. Individually, two of the SNPs associate significantly with cleft palate, as does the haplotype containing the rare allele of both SNPs. Analysis of the patient cohorts stratified for the presence of ankyloglossia significantly increases these associations. Reporter assays were used to analyse each of these haplotypes and the impact of individual SNPs. An important functional role for rs41307258 results in a decreased promoter activity of up to 50%. Conclusions: CPX-like patients harbouring this promoter haplotype are therefore associated with decreased TBX22 transcriptional activity. The risk haplotype, in concert with additional genetic and/or environmental factors, may contribute to the phenotypic variation observed and provide a novel causative mechanism for cleft palate, especially in patients with ankyloglossia.